Implementasi Marketing Syari’ah dan Inovasi Produk dalam Meningkatkan Kinerja UMKM di Kecamatan Talun Kabupaten Cirebon - Abdul Rosyid; Anton Sudrajat; Alvien Septian Haerisma; Enceng Iip Syaripdin; Udin Komarudin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to describe the implementation of sharia marketing and product innovation in an effort to improve the performance of MSMEs in Talun District, Cirebon Regency. The focus of the research is directed toward an in-depth understanding of marketing practices based on sharia values, the forms of product innovation developed, and how these two aspects contribute to improving business performance. The research method employed is a qualitative approach with a case study design, using data collection techniques such as in-depth interviews, observation, and documentation with MSME actors selected through purposive sampling. Data analysis was carried out through the stages of data reduction, data presentation, and conclusion drawing. The results of the study show that sharia marketing is implemented by MSMEs through the principles of honesty, transparency, friendly service, and the avoidance of practices that harm consumers. Product innovation is carried out through design improvements, enhanced material quality, product diversification, and adjustments to local market needs. These two strategies have been proven to strengthen customer trust, increase competitiveness, and encourage sales growth and business stability. This study emphasizes that integrating sharia values with product innovation is a strategic step for MSMEs in facing the dynamics of business competition. These findings are expected to serve as a reference for MSME practitioners, business facilitators, and policymakers in formulating MSME empowerment programs based on sharia principles and sustainable innovation.